2007
DOI: 10.1057/palgrave.crr.1550057
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Responsibility and Corporate Reputation: Two Separate Concepts or Two Sides of the Same Coin?

Abstract: The need to investigate the link between rep-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(124 citation statements)
references
References 39 publications
(49 reference statements)
3
109
0
8
Order By: Relevance
“…An advanced corporate reputation acts as both an intangible asset and a source of strategic advantage increasing companies´ long term ability to create value (Caves and Porter, 1977) since corporate reputation is composed of a company´s unique set of skills in delivering both economic and non-economic benefits (Fombrum, 1996). Sustainability is increasingly seen as a determinant of corporate reputation since firms show externally that they are aware of the need of managing a wider range of social and environmental issues (Friedman and Miles, 2001;Hillenbrand and Money, 2007). Furthermore, this concept is relied upon to enhance corporate reputation (Becker-Olsen et al, 2006;Pirsch et al, 2007) and academic literature has recently suggested that companies may use sustainability as a way to manage their reputation risk (Bebbington et al, 2008).…”
Section: The Importance Of Sustainability In Creating a Superior Corpmentioning
confidence: 99%
See 2 more Smart Citations
“…An advanced corporate reputation acts as both an intangible asset and a source of strategic advantage increasing companies´ long term ability to create value (Caves and Porter, 1977) since corporate reputation is composed of a company´s unique set of skills in delivering both economic and non-economic benefits (Fombrum, 1996). Sustainability is increasingly seen as a determinant of corporate reputation since firms show externally that they are aware of the need of managing a wider range of social and environmental issues (Friedman and Miles, 2001;Hillenbrand and Money, 2007). Furthermore, this concept is relied upon to enhance corporate reputation (Becker-Olsen et al, 2006;Pirsch et al, 2007) and academic literature has recently suggested that companies may use sustainability as a way to manage their reputation risk (Bebbington et al, 2008).…”
Section: The Importance Of Sustainability In Creating a Superior Corpmentioning
confidence: 99%
“…In this sense, CSR is one of the most prevalent topics concerning the social dimension studied in sustainability research (Lichtenstein et al, 2004). This vision is particularly interesting when one considers how the term CSR is sometimes used in a very narrow sense to represent charitable donations, community involvement and employee voluntarism (Hillenbrand and Money, 2007).…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, over the course of time, research has indicated that if managed effectively, community initiatives could assist companies in retaining and even increasing their customers (Levy, 2005;Simmons and Becker-Olsen, 2006), fostering a sense of commitment from employees (De Gilder et al, 2005;Grayson, 1993;Zappala, 2004) and strengthening their corporate reputation as a 'caring business' (Arendt and Brettel, 2010;Brammer and Millington, 2005;Brammer and Pavelin, 2005;Hillenbrand and Money, 2007). As a result, community initiatives have come to be perceived more as strategic activities rather than voluntary or discretionary (Saiia et al, 2003): that is to say, not legally mandated but strategically essential.…”
Section: Corporate Social Responsibility: Discretionary Strategic Ormentioning
confidence: 99%
“…Hillenbrand and Money (2007) Bhattacharya and Sen 2003) or on customer-based corporate reputation (e.g., Walsh et al 2009), yet it has overlooked the link between cause assessment, corporate philanthropy, and corporate reputation. Second, our research follows the call for a more nuanced understanding of corporate reputation (Walker and Dyck 2014).…”
mentioning
confidence: 99%